THE INFLUENCE OF PROBLEM BASED LEARNING MODEL TOWARDS STUDENT’S CREATIVE THINKING SKILL IN BIOLOGY GRADE X AT SMA NEGERI 2 SURAKARTA IN ACADEMIC YEAR 2011/2012 - Puspitasari, Laksmi; Santosa, Slamet; Harlita, Harlita (Prodi Pendidikan Biologi FKIP UNS, 2012)
ABSTRACT- This research aimed to ascertain the application of Problem Based Learning model towards student?s creative thinking skill in Biology at student of X grade of SMA Negeri 2 Surakarta in academic year 2011/2012. This research was a quasi experiment research. The research was designed using posttest only control group design using Problem Based Learning as model towards the experimental group, as compared to the conventional model. The conventional model was complemented with discussion, classical course and question-answer method. The population of this research was all of X degree students at SMA Negeri 2 Surakarta in academic year 2011/2012. The sample of this research was taken using cluster random sampling. The data was collected by using essays test, document and through observation. The stated hypotheses was tested using t-test. The conclusion of this research showed that the application of Problem Based Learning model has given significant effect towards student?s creative thinking skill in Biology at student of X grade of SMA Negeri 2 Surakarta in academic year 2011/2012. Keywords: Problem Based Learning Model, Creative Thinking Skill